Implementation gaps in culturally responsive care for refugee and migrant maternal health in New South Wales, Australia - Katarzyna Olcoń; Delia Rambaldini-Gooding; Chris Degeling (BMC, 2023)
Abstract Background Refugee and migrant women are at higher risk of childbirth complications and generally poorer pregnancy outcomes. They also report lower satisfaction with pregnancy care because of language barriers, perceived negative attitudes among service providers, and a lack of understanding of refugee and migrant women's needs. This study juxtaposes health policy expectations in New South Wales (NSW), Australia on pregnancy and maternity care and cultural responsiveness and the experiences of maternal healthcare providers in their day-to-day work with refugee and migrant women from non-English speaking backgrounds. Methods This study used a qualitative framework method to allow for a comparison of providers' experiences with the policy expectations. Sixteen maternal health service providers who work with refugee and migrant women were recruited from two local health districts in New South Wales, Australia and interviewed (November 2019 to August 2020) about their experiences and the challenges they faced. In addition, a systematic search was conducted for policy documents related to the provision of maternal health care to refugee and migrant women on a state and federal level and five policies were included in the analysis. Results Framework analysis revealed structural barriers to culturally responsive service provision and the differential impacts of implementation gaps that impede appropriate care resulting in moral distress. Rather than being the programmatic outcome of well-resourced policies, the enactment of cultural responsiveness in the settings studied relied primarily on the intuitions and personal responses of individual service providers such as nurses and social workers. Conclusion Authentic culturally responsive care requires healthcare organisations to do more than provide staff training. To better promote service user and staff satisfaction and wellbeing, organisations need to embed structures to respond to the needs of refugee and migrant communities in the maternal health sector and beyond.